Good Corporate Governance in Islamic Banking during Fourth Industrial Revolution Era - Delina Herdian Septiani; Linda Nurlaela; Arim Nasim; Elis Mediawati (Perhimpunan Intelektual Muslim Indonesia, 2022)
The purpose of this study is to analyze information about implementation of Corporate Governance in Islamic banking. This study uses a quantitative approach with a systematic literature review method from various journals. With the systematic literature review method, the authors identify all empirical evidence, where the identification aims to answer questions such as